Environmental economics : a critical overview - Gilpin, Alan. (Chichester ; New York : John Wiley, 2000)
This book to demonstrate thatwhile the prophets of doom and gloom have been largely confounded,there are in the greater distance still limitations to growth.
Includes bibliographical references (p. 305]-321) and indexes.
aia 3/05/13
Loan
Keywords: Sustainable development; Environmental economics